PROSPECTS FOR INDUSTRIAL DEVELOPMENT IN UZBEKISTAN - Fayziyeva, Shirin (THE INNOVATION ECONOMY, 2023)
This article describes the role of the industrial network of Uzbekistan in the national economy, its sustainable development, the economic efficiency of network development and development prospects.